বাংলাদেশের নারী চরিতাভিধান - জামান, সাঈদা 1957- (ঢাকা : বাংলাদেশ লেখক সংসদ, 1998)
Biographical dictionary of women of Bangladesh.
Includes index.
In Bengali.
Keywords: Women -- Bangladesh -- Biography -- Dictionaries; Bangladesh -- Biography -- Dictionaries